Outcome of neoadjuvant chemotherapy followed by concurrent chemoradiotherapy versus concurrent chemoradiotherapy alone in non-metastatic locally advanced non-small cell lung cancer – A prospective and randomized study - Subir Pal; Anjan Bera; Soumen Mukherjee; Asmita Dasgupta; Srikrishna Mandal; Saptarshi Banerjee (Asian Journal of Medical Sciences, 2023)
Background: Sequential chemoradiotherapy and concurrent chemoradiotherapy are two treatment options for locally advanced non-small cell lung cancer (NSCLC). Still there is limited data regarding which is the better treatment option. Aims and Objectives: This study is to compare the response rate and toxicity pattern between induction (neoadjuvant) chemotherapy followed by concurrent chemoradiotherapy versus concurrent chemoradiotherapy alone in locally advanced NSCLC patients. Materials and Methods: A total of 48 Stage III NSCLC patients were selected for the study and were randomized into two arms with a 1:1 ratio. Patients of ARM-1 received concurrent chemoradiotherapy alone of a total dose of 66Gy/33# over 6 and ⅟2 weeks with paclitaxel (50 mg/m2) and carboplatin (Area under curve [AUC] 2) once every week. The study arm (ARM-2) received two cycles of induction chemotherapy with paclitaxel (175 mg/m2) and carboplatin (AUC 6) every 3 weeks and concurrent chemoradiotherapy (same CRT as on ARM-1). Results: In our study, overall response rate (Complete response+Partial response) in Arm 1 and Arm 2 was 62% and 71%, respectively. The treatment was very tolerated in our study. A mean follow-up of 12 months by Kaplan–Meier survival analysis showed a statistically non-significant difference in disease-free survival in both arms. Progression-free survival was numerically superior in the induction chemotherapy arm but the difference was statistically non-significant. Acute hematological toxicity was numerically more in the concurrent chemoradiotherapy arm, but statistically not significant. Acute lung toxicity, acute pharynx, and esophagus toxicity were numerically more in the induction chemotherapy arm but statistically non-significant. Conclusion: There was no significant difference between induction chemotherapy followed by concurrent chemoradiotherapy and concurrent chemoradiotherapy alone in the present study population.